2018
DOI: 10.9755/ejfa.2018.v30.i3.1642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on photosynthesis and chlorophyll fluorescence of maize seedlings under salt stress

Abstract: The impact of arbuscular mycorrhizal fungi (AMF) Glomus. tortuosum on morphology, photosynthetic pigments, chlorophyll (Chl) fluorescence, photosynthetic capacity and rubisco activity of maize under saline stress were detected under potted culture experiments. The experimental result indicated the saline stress notably reduced both dry mass and leaf area in contrast with the control treatment. Nevertheless, AMF remarkably ameliorated dry mass and leaf area under saline stress environment. Besides, maize plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Fernández-Lizarazo and Moreno-Fonseca (2016) conclude that mycorrhiza can enhance the water potential, stomatal conductance and nutritional content of plants and finally result in an increase in plant growth during periods of drought. Also a higher dry mass and leaf area and enhancement of chlorophyll content, light energy absorption, gas exchange and Rubisco activity of plants inoculated with mycorrhiza growing under salinity stress is reported by Xu et al (2018). Corrêa et al (2006) report that the response of plants to mycorrhiza depends on "their age (stage of development, leaf area), their initial nutritional status and the amount of nitrogen supplied".…”
Section: Resultsmentioning
confidence: 94%
“…Fernández-Lizarazo and Moreno-Fonseca (2016) conclude that mycorrhiza can enhance the water potential, stomatal conductance and nutritional content of plants and finally result in an increase in plant growth during periods of drought. Also a higher dry mass and leaf area and enhancement of chlorophyll content, light energy absorption, gas exchange and Rubisco activity of plants inoculated with mycorrhiza growing under salinity stress is reported by Xu et al (2018). Corrêa et al (2006) report that the response of plants to mycorrhiza depends on "their age (stage of development, leaf area), their initial nutritional status and the amount of nitrogen supplied".…”
Section: Resultsmentioning
confidence: 94%
“…Photosynthesis, the key process of primary metabolism, is sensitive to salinity [5]. Salt stress can reduce the CO 2 availability by limiting diffusion through stomata and the mesophyll, 2 of 14 destroying the photosystems II (PS II) reaction center and disrupting electron transport from PS II to PS I [6][7][8]. These adverse effects lead to a decline in photosynthetic capacity and ultimately inhibit plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also used chlorophyll fluorescence analysis to evaluate the positive effect of AMF on the photosynthetic capacity of the host plant under salinity stress, including Oryza sativa [7], Jatropha curcas [11], and Zea mays [8]. Chlorophyll fluorescence is a rapid, non-destructive method to examine the stress features and photosynthetic performance of a plant [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mechanisms other than those studied must have been in operation. Several studies have demonstrated an improvement in gas exchange and fluorescence parameters following the application of AMF in horticultural crops [67][68][69], including tomato [70]. In our case, the low relative percentage of root colonization prevented greater changes in plant physiology from being observed.…”
Section: Discussionmentioning
confidence: 50%